Heavy metals in Kuala Lumpur municipal solid waste - Steven, Anthony Nyangson (2003)
Considering the advantages of Municipal Solid Waste Incineration over other alternatives for MSW generated by the residents of Kuala Lumpur, a study was carried out to determine the loads of heavy metals in the MSW. Direct determination from collected MSW samples was carried out using Atomic Absorption Spectrophotometer. In this project, arsenic, cadmium, lead, chromium and mercury were determined by AAS for the period of one year, beginning from July 2001 until June 2002. As the result, average heavy metal loads, in g per ton refuse (dry basis) are: Cd: 5.9 &on. Cr: 46.7 &on., Hg: 3.7 &on., Pb: 1 1 1.1 g/ton, and As : 3.4 &on The heavy metals emission for MSW incineration is expected to be lower than the referred standards for this project